Hubungan Efikasi Diri dengan Sikap Kader Nasyiatul Aisyiyah terhadap Program STOP Stunting di Kabupaten Boyolali - Shofia Andriyani; Kusuma Estu Werdani (Jurnal Kesehatan Masyarakat Indonesia, 2021)
Background: The STOP stunting program that has been launched by the leadership of Nasyiatul Aisyiyah has not run optimally because there are still obstacles in its implementation. Self-efficacy is one of the internal factors that can shape the attitude of Nasyiatul Aisyiyah cadres in carrying out the STOP stunting program to support the implementation of programs that are not yet running. Objective: To analyze the relationship between self-efficacy and the attitude of Nasyiatul Aisyiyah cadres towards the STOP stunting program in Boyolali Regency. Methods: This research is quantitative observational using aapproach cross sectional which was conducted in December 2020 involving 80 Nasyiatul Aisyiyah cadres. The variables in this study were self-efficacy and cadre attitudes. The primary data was obtained through a questionnaire, while the secondary data was obtained from the Boyolali District Health Office and the Nasyiatul Aisyiyah leadership. The analysis was carried out by univariate and bivariate using test chi square. Results: A total of 51.3% of cadres had low self-efficacy and 47.5% had poor attitudes towards the STOP stunting program and there was a significant relationship between self-efficacy and cadre attitudes (p=0.001). Conclusion: Self-efficacy is closely related to the attitude of Nasyiatul Aisyiyah cadres.